Pathological variants in HPV-independent vulvar tumours - Farkas, Sanja A.; Qvick, Alvida; Helenius, Gisela; Lillsunde-Larsson, Gabriella (Scientific reports, 2025)
Vulvar cancer is a rare gynaecological disease that can be caused by infection with human papillomavirus (HPV). The mutational frequencies and landscape for HPV-associated and HPV-independent vulvar tumor development are supposedly two distinctly different pathways and more detailed knowledge on target biological mechanisms for individualized future treatments is needed. The study included formalin-fixed paraffin-embedded (FFPE) samples from 32 cancer patients (16 HPV-negative and 16 HPV-associated), treated in Örebro, Sweden from 1988 to 2008. The Oncomine™ Comprehensive Assay v3 was used to detect variants across 161 different tumor relevant genes. Data analysis included quality assessment followed by variant analysis of DNA with the Oncomine Comprehensive v3 workflow and with a custom filter using the VarSome Clinical software. The RNA-analysis was performed with the Oncomine Comprehensive v3 workflow. Totally, 94% of DNA libraries and 81% of RNA libraries were of adequate quality for further downstream analysis. With the Oncomine™ filter chain there was an increased number of variants in the HPV-negative group (2.5 variants) compared to the HPV-associated group (1.5 variants). Using custom filter and the Varsome Clinical software; additional single nucleotide variants (SNV) were detected where the vast majority were classified as likely benign/benign. HPV-negative tumors had a larger fraction of variants of unknown significance (VUS), and likely pathogenic/pathogenic compared to the HPV-associated tumours. The top 10 frequently mutated genes in HPV-indepentent tumors were TP53 , POLE , PTCH1 , BRCA2 , CREBBP , NOTCH2 , ARID1A , CDKN2A , MSH2 , and NOTCH1. Three fusion genes were detected; TBL1XR1(1)::PIK3CA(2) ( n = 2) and NF1(5)::PSMD11(2) ( n = 1). Copy number variations (CNV) were more common in HPV-associated tumors ( n = 13/16, 81%) compared to HPV-negative tumors ( n = 9/14, 64%). The most frequent CNV was found in the cMYC gene, followed by CDK2 ( n = 5) and CDK4 ( n = 4). The main outcome of this study show that vulvar cancer harbour genetic variations of different types and specifically, HPV-independent tumours are molecularly very heterogeneous and harboured more SNVs while HPV-associated tumors more frequently presented with gene amplifications. The PI3K/AKT/mTOR1 pathway was affected in both the groups as well as the cell cycle regulation pathway. Similarly, the DNA repair gene POLE was found mutated in both vulvar cancer groups.